Short-term follow-up after percutaneous patent ductus arteriosus occlusion between low and high weight pediatric patients: a single center experience (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Device occlusion is a preferred treatment for patent ductus arteriosus (PDA) in adult and children patients; however, the exact limit of body weight requirement has not been established. This study aimed to describe the outcome and safety of transcatheter PDA occlusion in low and high weight pediatric patients. METHODS This was a retrospective study in Sanglah Hospital, Denpasar, Bali, Indonesia, in patients aged <12 years who had undergone transcatheter PDA occlusions from 2010 to 2017. Data were obtained from the registry including baseline characteristics (age, sex, body weight, and height), procedural-specific data (PDA characteristics, pulmonary and systemic pressures, and flow ratio intra-procedure), and procedural complications. Success rate and adverse events at 24 hours, 1 month, and 3 months after the procedure were assessed. RESULTS A total of 175 subjects were grouped into two categories: low weight, ≤6 kg (n = 50) and high weight, >6 kg (n = 125). The success rates (complete closure) in the ≤6 and >6 kg groups were, 90.0% and 75.9% at 24 hours follow-up, 92.9% and 85.5% at 1 month, and 95.8% and 91.1% at 3 months, respectively. Major complications related to the procedure in patients ≤6 kg included transient dysrhythmia (n = 6) and massive bleeding (n = 2), and complications in patients >6 kg were transient dysrhythmia (n = 14), massive bleeding (n = 1), embolization (n = 1), and death (n = 1). CONCLUSIONS Transcatheter PDA occlusion had similar success rate and safety in both low and high weight pediatric patients.